EFFECTS OF DIFFERENT LEVELS OF DAPHNIA AND ARTEMIA EXTRACTS ON FOOD ACCEPTABILITY AND GROWTH FACTOR RATES OF BELUGA (HUSO HUSO LINNAEUS, 1758) - K. Darvish; M. Sodagar; M. Imanpor; A. Taheri (Iranian Fisheries Research Organization, 2008)
In a 30 day feeding trial, daphnia and Artemia extracts were added to diets of juvenile Beluga (Huso huso) at different levels to evaluate its effects on growth and survival rate of the fish. The trial was carried out in aquaculture research center of the Gorgan University, during which three different dietary levels of extracts (1:25, 1:50 and 1:100) were used in 250 liter PVC tanks filled with about 125 liters of water. A total of 20 juvenile Beluga with an average weight of 5±0.2 geach was stocked in tanks and were fed 4 meals a day. Growth and survival factors were analyzed at the end of the trial period. The results showed that the addition of extracts in diets led to improvement of body weight increase, weight increase percentage, specific growth rate (SGR), daily growth rate (DGR), daily growth index (DGI), condition factor (CF), price index (PI) and decrease of food conversion ratio (FCR) compared to the control treatment. The best improvement of growth index was achieved at the dietary level 1:50 Artemia extracts. There was no significant difference (P>0.05) in survival among treatments.